Side Effects of Thrombolytic Treatment with Porcine Plasmin and Low Dose Streptokinase - Marbet, G A; Eichlisberger, R; Duckert, F; Ritz, R; da Silva, M A; Biland, L; Widmer, L K; Schmitt, H E (Thrombosis and Haemostasis, 1982)
In the sequential thrombolytic therapy with porcine plasmin and low dose streptokinase side effects are mainly due to bleeding, intolerance reactions are less important. Treatment had to be prematurely stopped in 42 (37%) of 114 DVT cases because of severe bleeding and in 12 (10%) due to intolerance reactions. The corresponding figures for the 45 cases with arterial occlusions are 15 (33%) and 2 (4%) respectively. The intensity of systemic proteolysis as represented by the thromboplastin time is significantly correlated with haemorrhagic manifestations. Macrohaematuria and bleeding from puncture sites are the most frequent haemorrhagic complications followed by spontaneous bleeding into skin and muscles. Non-fatal intracranial bleeding occurred in 1 DVT case (0.9%) and in 2 patients with arterial occlusions (4.4%). The benefit of this potent thrombolytic regimen would greatly improve if a strong reduction of premature treatment stop could be achieved.
Keywords: Thrombolysis side effects; Low dose streptokinase; Porcine plasmin; Bleeding; Streptokinase intolerance